Platone e gli Eleati (II) - Lucarini, Carlo M. (Hyperboreus, 2018)
Plato gives two constrasting accounts of Zeno’s philosophical purposes in the Phaedrus and Parmenides. The Parmenides is more accurate in detail, and consequently it is more probable that Zeno intended to defend Parmenides’ teaching, as he is represented as doing in this dialogue, than to accumulate eristic contradictions for their own sake, as he is represented as doing in the Phaedrus. Plato seems to be aware that one of the main features of Socratism, dialectic reasoning, originates in Eleatism; also that the distinction between the sensible and intellegible worlds (another chief feature of Socratism, as well as of Platonism) had been anticipated by Parmenides. Despite these considerable debts to Eleatism, Plato’s Eleatic dialogues (the Parmenides and the Sophist) aim rather at uncovering the shortcomings of Eleatic logic. Plato was probably aware that eristic originated in Parmenides’ infelicitous assertions about εἶναι, but it was not his well-known dislike for eristic that prompted him to write the Parmenides and the Sophist: his polemic against Eleatism originates rather from the fact that some contemporary philosophers (probably the Megarians) were still using Eleatic logic. Also the εἰδῶν φίλοι (probably a group of Academics) adopted some important features of Eleatism: attacking Parmenides, Plato pointed out to his Megarian and Academic friends how many drawbacks Eleatic logic entailed.